Chemical Modification of Chitosan for Metal Ion Removal - Zakia S. Mohsin (Journal of Global Pharma Technology, 2018)
This study is interested with a significant application of surface chemistry in the fields of treatment of pollution. It deals with adsorption systems of chemical pollutants(some heavy metal ions) on surface (modified chitosan).Atomic absorption spectrophotometry technique have been used to results adsorption data at different conditions of (contact time, pH).Chitosan were modified from benzoyl chloride reaction with ammonium thiocyanate and then its resulting composite reactor with carboxylic acids at room temperature, the chemical structures of modified polymer was to elucidated using FTIR and 1HNMR. Chitosan modified compounds have been evaluated as a good material for adsorption of heavy elements in water solutions.